Strategi Multiple Intelligences dalam Pembelajaran Pendidikan Agama Islam - Dewi, Yelfi (Universitas Islam Negeri Imam Bonjol Padang, 2023)
Education is one of the indicators to create a civilized human being. Every human being has intelligence where the basic intelligence describes the essence of the self or the wholeness of the self. Without one of them, a person cannot be a complete and integrated person. Learning strategies play an important role in accommodating the fulfillment of this in order to reach almost all intelligences possessed by students. In the process, learning must have patterns and elements of grammar management, sequence, logic, order and sequence, problem solving, mapping, individual experience, and social relationships through interaction and discussion. To fulfill these needs, the selection of learning strategies based on multiple intelligences is very appropriate to be a determining factor in the success of the learning process